2009
DOI: 10.1080/10715760903071649
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bcl-2 phosphorylation in response to oxidative stress in cardiac myocytes

Abstract: Oxidative stress promotes cardiac myocyte death and has been implicated in the pathogenesis of many cardiovascular diseases. Bcl-2 family proteins are key regulators of the apoptotic response, while their functions can be regulated by post-transcriptional modifications including phosphorylation, dimerization or proteolytic cleavage. This study used adult cardiac myocytes to test the hypothesis that activation of specific kinase signalling pathways by oxidative stress may modulate either the expression or the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Also, the current study revealed marginal induction of JNK1/2 during Bcl-2 upregulation that supported the inverse relationship of Bcl-2 and JNK1/2 expression. This has been reinforced by other reports which show that the stimulation of cardiac myocytes with 0.2 mM H 2 O 2 induces apoptosis with a marked downregulation of Bcl-2 protein (Markou et al 2009). Dunschede et al (2008) have reported that Bcl-2 upregulation may protect against the postischemic burst of ROS and therefore suppresses apoptotic-related cell death.…”
Section: Bcl-2 Upregulation Is Required For the Inhibition Of Hepatocsupporting
confidence: 56%
“…Also, the current study revealed marginal induction of JNK1/2 during Bcl-2 upregulation that supported the inverse relationship of Bcl-2 and JNK1/2 expression. This has been reinforced by other reports which show that the stimulation of cardiac myocytes with 0.2 mM H 2 O 2 induces apoptosis with a marked downregulation of Bcl-2 protein (Markou et al 2009). Dunschede et al (2008) have reported that Bcl-2 upregulation may protect against the postischemic burst of ROS and therefore suppresses apoptotic-related cell death.…”
Section: Bcl-2 Upregulation Is Required For the Inhibition Of Hepatocsupporting
confidence: 56%
“…Considering that apoptosis was induced in cancer cells in a short time after OA treatment, we focused our study on if p38 MAPK phosphorylated and activated pro-apoptotic proteins in OA-stimulated cancer cells. To date, phosphorylations of Bax, Bim and Bcl-2 by p38 MAPK have been reported to facilitate the induction of apoptosis (Rosini et al, 2000;Cai et al, 2006;Capano et al, 2006;Kim et al, 2006;Markou et al, 2009). The early phosphorylation (3-6 hr after stilumation) of apoptosisrelated proteins Bax, Bim and Bcl-2 was detected in cancer cells treated with OA, as well as the subsequent translation of Bax and Bim ( Figure 4A and 4B).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, pretreatment with MG132 suppresses BCL2 down-regulation in quinacrine-treated cells. Previous studies revealed that activation of p38 MAPK by oxidative stress results in the phosphorylation and degradation of BCL2 (Markou et al, 2009). Moreover, dephosphorylation of BCL2 by protein phosphatase 2A protects BCL2 from proteasomedependent degradation .…”
Section: Resultsmentioning
confidence: 99%